1999
DOI: 10.1677/jme.0.0230209
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone effect on growth and growth mediators of the GH-IGF-I axis in the liver and epiphyseal growth plate of juvenile rats

Abstract: Several studies have suggested that testosterone may have a direct, GH-independent effect on growth. In order to assess possible mechanism(s) whereby testosterone exerts its growth-promoting effect, we evaluated its effect on growth mediators of the GH-IGF-I axis, in both the liver and the epiphyseal growth plate (EGP). Testosterone was administered to peripubertal rats and the responses of mRNA of GH receptor, IGF-I, IGF-I receptor and IGF-binding proteins-1 and -3 (IGFBP-1 and IGFBP-3) as well as circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
(59 reference statements)
1
21
0
1
Order By: Relevance
“…Testosterone (T enanthate; 300 mg im, each week) administration increased serum IGF-1 concentrations in healthy men after 6 weeks of treatment; however, treatment with exogenous steroids (nandrolone decanoate; 300 mg im, each week) did not change serum levels of IGF-1 but did decrease the level of the serum IGF-binding protein-3, potentially increasing the level of bioavailable IGF-1 in the nandrolone subjects [21]. In contrast to these studies in humans, testosterone administration to juvenile rats, has been reported to significantly decrease circulating levels of IGF-1 [15]. We did not analyzed the serum IGF-1 levels, however, previous results confirmed that there was a negative correlation between TT levels in rats treated with high doses of testosterone and serum IGF-1 [15].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Testosterone (T enanthate; 300 mg im, each week) administration increased serum IGF-1 concentrations in healthy men after 6 weeks of treatment; however, treatment with exogenous steroids (nandrolone decanoate; 300 mg im, each week) did not change serum levels of IGF-1 but did decrease the level of the serum IGF-binding protein-3, potentially increasing the level of bioavailable IGF-1 in the nandrolone subjects [21]. In contrast to these studies in humans, testosterone administration to juvenile rats, has been reported to significantly decrease circulating levels of IGF-1 [15]. We did not analyzed the serum IGF-1 levels, however, previous results confirmed that there was a negative correlation between TT levels in rats treated with high doses of testosterone and serum IGF-1 [15].…”
Section: Discussionmentioning
confidence: 75%
“…The results of in vivo and in vitro experiments indicate that insulin-like growth factor (IGF)-1 is an important growth factor which, by its receptors, mediates cardiac growth in a PI-3K dependent manner [12,13]. However, the precise role of IGF-1 in the regulation of cardiac structure under both physiological stress and the direct effect of testosterone remains debatable [14,15,16].…”
Section: Experimental Animals and Hormonal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar effect occurs in the growth plates of hypophysectomized rats [61]. Testosterone, therefore, modulates the peripheral action of GH on the growth plate and liver by enhancing GHR expression.…”
Section: Gh Actionmentioning
confidence: 78%